Modulation of stability and functionality of a phyto-antioxidant by weakly interacting metal ions: curcumin in aqueous solution. Issue 124 (30th November 2015) - Bagchi, Damayanti; Chaudhuri, Siddhi; Sardar, Samim; Choudhury, Susobhan; Polley, Nabarun; Lemmens, Peter; Pal, Samir Kumar
Abstract : Metal exchange process in metallo–curcumin leading to duality in action: enhancement of both aqueous stability and anti-oxidant property. Abstract : The natural polyphenol curcumin and its metal coordinated complexes show obvious benefits in the medical therapies of cancer and several neurodegenerative diseases. On the other side their stability and bioavailability are critical issues. The present study is an attempt to address the stability and functionality of curcumin upon complexation with transition metal ions. We have synthesized and optically characterized metallo–curcumin complexes with Cu(ii ) and Zn(ii ). From femtosecond resolved upconversion studies an interaction at the molecular level is revealed based on an observed photoinduced electron transfer from curcumin to the metal ions. In order to investigate the antioxidant activity of the complexes, we have performed a 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay in dark. The Cu(ii )–curcumin complex exhibits an enhanced and recyclable activity, more pronounced compared to that of the Zn(ii )–curcumin complex, which can be attributed to the weaker O–H bond present in the former case. In contrast, the Zn(ii ) complex has a higher solubility and stability in aqueous media than the Cu(ii ) complex. To address stability vs. functionality issues, we have suggested a facile method that enhances the solubility and stability of curcumin in aqueous media by metalation with Zn(ii ) and a successional replacement of Zn(ii ) in the complex by Cu(ii ) through a simple route to enhance the activity prior to its use. We have also used the complex in a model anti-bacteriological assay experiment where it shows significantly higher activity compared to pure curcumin. The dichlorofluorescin (DCFH) oxidation indicates an enhancement in ROS generation, which in turn is responsible for the enhanced antioxidative property of the Cu(ii )–curcumin complex. Our results provide a promising method to use metallo–curcumin complexes in diverse biological applications.